6 months of radioxenon detection in western Europe with the SPALAX-New generation system - Part1: Metrological capabilities. (December 2020) - Topin, Sylvain; Gross, Philippe; Achim, Pascal; Generoso, Sylvia; Cagniant, Antoine; Delaune, Olivier; Morin, Mireille; Philippe, Thomas; Fontaine, Jean-Pierre; Moulin, Christophe; Douysset, Guilhem; Le Petit, Gilbert
Abstract: The SPALAX-NG is a new-generation system that is designed to detect radioactive xenon at trace levels in the atmosphere following a nuclear explosion or civilian source release. This new system formed part of a validation program led by the Provisional Technical Secretary of the Comprehensive Nuclear-Test-Ban Treaty (CTBT) Organization. In this study, the first SPALAX-NG unit was tested for six months between October 2018 and April 2019 at the CEA/DIF premises near Paris, France. This test period provided an outstanding opportunity to illustrate the high level of detectability and reliability of the system. The data availability obtained over this period was approximately 99%, which was well above the CTBT Data Availability criteria of 95%. The data reliability was demonstrated by a comparison with a collocated SPALAX-1 unit (former version of SPALAX) and by re-measuring several samples at the CTBT-certified French laboratory FRL08. The high sensitivity to the detection of the four relevant radioxenon isotopes was fully demonstrated and enabled the recording of a major dataset for western Europe. A large set of isotopic ratios was measured, which enabled the discrimination criteria between civilian sources and nuclear test signatures to be refined. Highlights: The first SPALAX-NG was tested for 6 months at the CEA/DIF premises near Paris. High detectability of radioactive xenon and high data reliability were demonstrated. An original dataset for western Europe has been recorded. The data enable the discrimination criteria of radioxenon to be refined.